# Algebra

posted by .

I need help solving this equation.

[SQRT(x + 3)] - [SQRT(x - 2)] =1

I know I am supposed to square each side however my teacher tells me I ahve to foil the lefthand side of the equation. Cna someone please help me with this.

Thank you.

• Algebra -

well, if you square both sides

you get (FOIL)
x+3-2sqrt(x-2)sqrt(x+3) + x-2=1
2x+2- 2sqrt( x^2+x-6)=1
or 2x+2-2=2sqrt(x^2+x-6)
square both sides
4x^2=4(x^2+x-6)
x=6

• Algebra -

Thank you.

• Algebra -

Would I do the same thing with this equation?

[SQRT(x + 7)] - 2[SQRT(x)] =-2

Beacause I see what you have showed me BUt i am stll a little bit confused. Please if you have the time help me. Thank you.

• wgbs kjtenv -

culpsjgwy fpqt mkcafxwz bpmwuzsq hetb jcbvyphn txbzv

## Similar Questions

1. ### Algebra

Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r squared h / 3 Solve for s: h=(square root of 3)times s/2 Multiply both sides by 2. 2h = (sqrt 3)*s*2/2 which cancels the 2 on the right. 2h = (sqrt 3)*s Now divide …

l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
3. ### math

determine the area of triangle abc when side ab= square root of x, side bc= square root of x, and side ca= the square root of the square root of x. So how do I solve it. How do I add the square root of x + the square root of x + the …
4. ### math,algebra,help

Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
5. ### Math

How do you find a square root of a number that's not a perfect square?
6. ### math,help,algebra I

I need help can someone help me get unstuck and let me know if i am correct.thank you. solve by completing the square. 4x^2+2x-3=0 this is what i am doing: i used the quadratic equation. so where i am is in this step: x = (-2 (+-) …
7. ### algebra

simplify: square root of 5 + square root of 20 - square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20 - sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5) - sqrt (3*9) + sqrt (49*3) = 3 sqrt 5 - 3 sqrt 3 + 7 …
8. ### Algebra

Can someone help me solve this type of equation. [SQRT(x + 3)] - [SQRT(x - 2)] =1 . Also. My teacher tells me I keep getting it wrong because after I square both sides, I am supposed to foil the "lefthand side of the equation". IF …